2008
DOI: 10.1007/s11224-008-9384-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl esters of coumarin-3-phosphonic acid and 1,2-benzoxaphosphorine-3-carboxylic acid: crystal structure, spectroscopic and theoretical elucidation

Abstract: IR-spectroscopic characterization of the coumarin-3-phosphonic acid and 1,2-benzoxaphosphorine-3-carboxylic acid ethyl esters has been carried out by means of linear-polarized IR (IR-LD) spectroscopy of oriented colloid suspensions in a nematic host. Quantum chemical DFT calculations at the B3LYP level of theory and 6-311??G** basis set were performed. The electronic structure and vibrational properties of both compounds are discussed. The spectroscopic data for 2-benzoxaphosphorine-3-carboxylic acid ethyl est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Their complexation ability in respect to different metal ions has been studied and discussed widely in a considerable number of investigations [5][6][7][8][9]. It has been found that the binding of a metal to the coumarin moiety retains or even enhances its biological activity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Their complexation ability in respect to different metal ions has been studied and discussed widely in a considerable number of investigations [5][6][7][8][9]. It has been found that the binding of a metal to the coumarin moiety retains or even enhances its biological activity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the next paper Koleva et al [313] used infrared spectroscopy to characterize the ethyl esters of coumarin-3-phosphonic acid and 2-benzoxaphosphorine-3-carboxylic acid, the latter as its P-oxide. The authors also performed quantum chemical DFT calculations on these species.…”
Section: Issuementioning
confidence: 99%
“…1,2 As a part of our systematic study on the synthesis, 3-10 spectroscopic, and structural characterization of novel coumarins, [8][9][10] their salts, and metal complexes [11][12][13][14][15][16][17][18] with potential biological activity, [1][2][3][4][5] we are presenting here the crystal structure and spectroscopic properties of novel (2-oxo-2H-chromen-3-yl)phosphonic acid monoethyl ester trihydrate, shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%